2006
DOI: 10.1021/ac051592c
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of Poly(dimethylsiloxane)-Based Valves for Interfacing Continuous-Flow Sampling to Microchip Electrophoresis

Abstract: This work describes the fabrication and evaluation of a poly(dimethyl)siloxane (PDMS)-based device that enables the discrete injection of a sample plug from a continuous-flow stream into a microchannel for subsequent analysis by electrophoresis. Devices were fabricated by aligning valving and flow channel layers followed by plasma sealing the combined layers onto a glass plate that contained fittings for the introduction of liquid sample and nitrogen gas. The design incorporates a reduced-volume pneumatic valv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 45 publications
1
75
0
2
Order By: Relevance
“…The performance of the microelectrodes was demonstrated by the separation and dual electrode detection of neurotransmitters and it was found that addition of SDS to the buffer system significantly improved detection limits and collection efficiencies. Future work will involve coupling these dual microelectrodes with PDMS-based valving schemes that interface continuous-flow sampling with microchip electrophoresis [8], with the long-term goal of monitoring the stimulated release of dopamine and norepinephrine from PC 12 cells on-chip [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the microelectrodes was demonstrated by the separation and dual electrode detection of neurotransmitters and it was found that addition of SDS to the buffer system significantly improved detection limits and collection efficiencies. Future work will involve coupling these dual microelectrodes with PDMS-based valving schemes that interface continuous-flow sampling with microchip electrophoresis [8], with the long-term goal of monitoring the stimulated release of dopamine and norepinephrine from PC 12 cells on-chip [32].…”
Section: Discussionmentioning
confidence: 99%
“…There are many advantages in utilizing this technique, including the ability to perform high-throughput screening [5], use of minute amounts of reagent and sample [6], fast analysis times [7], and the ability to integrate multiple processes [8]. Although much progress has been made in this area, there is still a need for the development of sensitive and selective detectors for bioanalytical applications.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com a complexidade das conexões entre os canais, os esquemas de mobilização dos fluídos podem envolver diversas concepções e estratégias para o controle seletivo do fluxo, desde a introdução de válvulas integradas 57,58 , ou simplesmente usar uma bomba pneumática posicionada externamente para a mobilização dos fluídos 59 .…”
Section: Instrumentaçãounclassified
“…Embora em sistemas convencionais a introdução da amostra seja realizada por ações eletrocinéticas e/ou hidrodinâmicas, em sistemas miniaturizados, devido à maior facilidade de implementação, esta etapa se faz predominantemente por processos eletrociné-ticos 70,71 . No entanto, alguns artigos relacionados à injeção hidrodinâmica em microchips podem ser encontrados na literatura 57,72,73 . A importância da introdução de amostra deve-se ao fato de que as características da zona de amostra determinam a qualidade da separação analítica.…”
Section: Introdução Da Amostraunclassified
“…Nowadays, various polymeric materials [16] are used such as PDMS [17,18], PMMA [19,20], polycarbonate [21], poly(ethylenterephthalate) [22,23], thermoset polyester [24,25], and polyester toner [26,27], Zeonix/ Zeonor [28,29] or thermoplastic olefin polymer of amorphous structure [7,30,31].…”
Section: Introductionmentioning
confidence: 99%